TI_GERICHTE 34.2006.30 vom 2. Juni 2006 , Divisione di prestazione di libero passaggio tra eredi di un assicurato defunto - TI Tribunale d'appello (2006)
Divisione di prestazione di libero passaggio tra eredi di un assicurato defunto